Economic recovery and long-run growth: Agenda for reforms - Alburo, Florian A. (Animo Repository, 1986)
The package of structural reforms contained in this report addresses the need both for economic recovery in the near-term and stable growth in the long run. It is being proposed to the new regime as a possible framework for that preparation of a development plan and for the formulation of more specific policies. The proposals have ·been drawn up with the intention that they (1) be mutually consistent, (2) proceed from a realistic assessment of the situation, and (3) have a common commitment to a set of guiding principles, namely; respect for human rights, social justice and poverty alleviation, a recognition. of the urgency of growth and greater efficiency, and a minimum of government intervention. Certain vital reforms have to be implemented in the short run both to reverse the sharp economic decline ·and to set the stage for implementing a more forward-looking development strategy. The bulk of these reforms aim simply at undoing the biases and penalties carried over from the previous regime. These include: External Debt - The approach· to managing external debt should proceed from what is required for reasonable growth, not what the creditors impose. With a decline in real GNP of 10 percent in the last two years, it is time the government refuse to subordinate growth to an overly burdensome debt service. Monetary Policy - To insure stability and efficiency of the financial system, reforms in monetary policy should be effected including the following: the independence of the Central Bank from political and other interest groups must be reasserted and preserved; Central Bank functions should be limited to the stabilization of prices, interest rates, and exchange rates in the short-run; the Central Bank should not participate in development finance or issue its own interest-bearing bills (e.g. Jobo bills). To promote economic recovery, monetary policy should be expansionary. In the past, monetary policy bad been excessively contractionary -- giving more emphasis on debt servicing rather than on growth. Fiscal Policy - We call for a reduction in the scope of government, which may require government reorganization, a downscaling, abolition, or merger of some offices. We propose a tax structure that relies more on direct than on indirect taxes; local government finance consistent with the spirit of decentralization. Government should intervene only when it can do better. Government Structure - The key reforms proposed, include decentralization i.e. devolution of power and authority (including broadened tax sourcing); checks and balances. Distributive Justice -·Expansion of the scope of land reform to include all natural resources and crops. If distributive justice is to be achieved, the government should commit itself to poverty targets. Monitoring should be undertaken not bythe regular government statistical offices but also by the private sector Population and Basic Services - Education, health, housing and social services call for individual and collective reforms to respond to the poverty alleviation objective and, at the same time, to improve the prospects for recovery and sustained growth. In order to allow greater benefits from growth and to make up for recent slippage, a strong commitment to population policy should be enunciated. Social service should receive a much greater share of the government’s budget. 7. Labor and Employment - Changes in the manner of wage setting are necessary to promote employment. We must do away with mandatory wage setting and opt for wider information access (by both management and labor) as a basis. therefor. We must strengthen collective bargaining and voluntary arbitration as a basis for settling labor-management disputes, For recovery, emergency employment assistance (preferably financed by external donors) should be provided to as in any unemployed to undertake infrastructure work in support of agriculture and rural development. 8. Trade - There should be a more open trade regime, with an exchange rate that reflects the real conditions of the market. Liberalization should be pursued quickly while a battery of consumption taxes is enacted. These reforms intend to achieve a more liberal and more neutral policy regime that allows for growth. Yet leaves it to private initiative to explore and reveal the areas of true economic promise, with a minimum of government direction and intervention. The direct economic role of government is not envisioned to be large, although it will be significant in such areas as social justice, the dissemination of information, and the support of research and technology. As distortions are removed and the debt-burden is reduced, we fully expect formerly penalized sectors to make-a larger contribution to growth. The implementation of these reforms will, therefore, naturally lead to a development strategy that is employment-oriented and rural-based. The government should support this course of evolution by redirecting its infrastructure programs towards the rural areas. In the same manner, for trade and industry, we expect industrial growth and restructuring to occur which rely on competitiveness both at home and abroad, and are supportive of rural development.